Navigating family estrangement. Helping adults understand and manage the challenges of family estrangement. - Engelbrecht, Lambert K. (Social Work/Maatskaplike Werk, 2025)
In Navigating Family Estrangement, psychotherapist and estrangement specialist Karl Melvin provides an insightful and practice-oriented exploration of this subject. Structured into thirteen chapters across four parts, the book examines how estranged adults can be effectively supported through a variety of professional perspectives.